High-frequency conductivity of multilayer graphene and graphite under the conditions of quantum cyclotron resonance - Kozlov, IV (2014)
The conductivity tensor of a layered conductor with the Dirac-type energy spectrum of charge carriers placed in a quantizing magnetic field under the condition of normal skin-effect is investigated using the method of quantum kinetic equation. It is shown that under the cyclotron resonance conditions there appear high-temperature quantum oscillations of conductivity, which are weakly sensitive to thermal broadening of the Fermi level. We present the expressions for the classical and high-temperature contributions to the conductivity tensor which determine the conductivity in the range of not too low temperatures where the Shubnikov–de Haas oscillations are vanishing.